Bronzos plitimas rytiniame Pabaltijo regione iki Kristaus - Luchtanas, Aleksiejus; Sidrys, Raimundas Vytenis (Archaeologia Lituana, 1999)
Small amounts of imported bronze weapons and tools began to reach different cultures in the East Baltic region by the 16th century BC, and locally made axes appear some two centuries later. The distribution of bronze artifact mass in the East Baltic, and adjacent west Poland, gives the impression that the metal arrived for the most part from western and southwestern sources. As local foundries did not smelt imported ore, but simply recast small quantities of imported scrap and broken tools, advancements in metalworking technology throughout the bronze age were minimal.Bronze was brought to the southeast Baltic by boat, or by coastal land routes, from Pomerania, north Germany and Denmark, during all three periods: Early Bronze Age (EBA: 1600–1100 BC), Late Bronze Age (LBA: 1100–550 BC), and Early Iron Age (EIA: 550 BC-0). Estonia was probably reached by direct boat routes from Sweden, from the end of the EBA onwards. We were surprised to find that relatively little bronze was found in territory along the major rivers of the East Baltic, including the Vistula, Nemunas and Dauguva, but the implications for river transport are not entirely clear.A narrow strip of coast, 20 km in width, representing 8% of the study area (including the islands of Estonia), accounted for an average 40% of the entire bronze index-value during the three periods. The sector of coast rich in drift amber, representing only 2% of the study area, accounted for about a third of the index-value. The role of this “amber coast” was greatest during the EBA, when the small strip used about 43 times more bronze than did the inland early brushed ceramic culture. Circum-Baltic bronze traffic from Pomerania to Estonia reached its peak in the LBA. At that time, some 939 bronze artifacts are known from 296 find-spots. In comparison to the EBA, find-spots increased by 45%, the bronze index-value by 70% and number of artifacts by 114%. Members of the Baltic barrow culture, who settled the Sambian coast with its immense deposits of drift amber, bartered for bronze with proto-germanic traders. They also acted as middlemen in selective down-the-line distribution of bronze goods to neighboring cultures: there was much bronze exchange with neighboring coastal areas, but far less with the inhabitants of the inland forests.Evidence exists that the circum-Baltic bronze trade of the LBA influenced the evolution of the proto-Baltic language. According to glottochronology, the first internal divergence within the baltic languages occurred relatively quickly, less than 400 years after the “birth” of the baltic family as it split away from balto-slavic, while the second great differentiation took place only after the passage of another 1250 years. The sequence of linguistic events coincides remarkably well with the pattern of regional bronze import: by the LBA, the west baits (or proto west baits) were in the circum-Baltic trade stream, with much exposure to new languages, ideas and 38 materials from west Europe, while the inland brushed ceramic culture remained distant and isolated from international traffic, and dialectal change was slow and conservative. It is not unreasonable to suggest that at the start of the bronze epoch there was a lingua franca among metal traders, which led eventually to the acceptance of germanic lexica related to trade, metal and social hierarchy into other west baltic dialects.Bronze import drops sharply during the EIA: findspots fall by a third to 198, and the aggregate bronze index-score is halved. A combination of extra-regional factors are responsible: amber’s fall from fashion in the general European market, the widespread technology replacement of bronze by iron in west-central Europe, and scythian-sarmation blockage of north to south trade routes. The diminishment of the Sambian peninsula’s traditional gateway role dominoed into an economic and cultural stagnation for the entire region.Through time, there is a clear shift in preference for certain types of bronze artifacts (Figure 15). In the EBA, about 79% of the total index-value is represented by weapons, 18% by ornaments and personal cosmetic items, and 1% by tools. Metal artifacts arriving in the East Baltic, mostly axes, are being channeled to male prestige needs. By the LBA, the index-value of weapons decreases to 59%, and the functions of other bronze artifacts diversify: 29% are ornaments and cosmetic items and 9% are tools. Production of bronze weapons decreases even further by the EIA; they now comprise only 9% of the total index-value. It is important to note that this decrease is not due to the introduction of iron weapons, which are extremely rare at this time. Rather, the “gap” in bronze weapons is filled by stone axes, and projectile points of bone and horn, the typical inventory of contemporary fortified settlements.The gradual increase in popularity of bronze ornaments, culminating in their 89% share of the entire EIA index-value, is understandable. Bronze is an attractive, highly reflective, relatively soft and easily worked material that is optimally suited for the production of elaborate ornaments. Having found its proper market niche, bronze ornaments continue to be an important female accessory in East Baltic culture for approximately tile next two millennia, as female burials accompanied by a kilogram, or more, of bronze and brass ornaments are found up to the 12th century A.D.The experimental manufacture at the end of the EIA of ornaments such as pins and La Tene style fibulae from locally available bog iron is an interesting phenomena. This “inappropriate” application of iron to jewelry at the onset of the iron age, parallels the “inappropriate” usage of bronze for axes at the start of the bronze age. In both cases, a newly introduced material is initially used and accepted, by happenstance or by experiment, for certain functional forms, and later is redirected towards more suitable forms which provide a better fit between component substance and function.The very low percentage of bronze tools in all periods (the average index-value is about 5%) clearly indicates they had no real role in production at this time in the East Baltic. But, as elsewhere in peripheral Europe (Milisauskas 1978: 208), even the relatively more common weapons, ornaments and personal cosmetic items of bronze were never really numerous enough to be used by the average warrior or woman. Bronze in the East Baltic was first and foremost an impressive reflective substance, which quickly occupied and long maintained a prestigious and authoritative material niche, exploited by village warriors and elders to help construct their status.